2021
DOI: 10.3233/shti210687
|View full text |Cite
|
Sign up to set email alerts
|

Standardised Holographic Patients: An Evaluation of Their Role in Developing Clinical Reasoning Skills

Abstract: In 2019, two standardised holographic patients viewed through a mixed-reality (MR) HoloLens headset were used in a structured learning activity to develop clinical reasoning skills among second-year nursing students (N=99, 94%). Quantitative results indicated that all students felt that being able to closely view holographic patients enhanced their learning experience. Qualitative results showed that the best feature of the MR technology was being able to clinically assess the patient in a safe facilitated env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Most participants opined that HoloLens was helpful for learning; however, the results indicate that factors such as unfamiliarity with the English language version and lack of environmental support can negatively affect students’ immersive learning experience. Similar to studies in New Zealand and Ireland ( Collins & Ditzel, 2021 ; Saab, Hegarty, Murphy, & Landers, 2021 ), this study demonstrates that nursing education with MR learning has advantages, especially in allowing students to visualize a holographic image of a patient and practice care provision in a safe environment. Additionally, this finding highlights the potential of MR as a tool for enhancing patient care in nursing practice ( Saab et al, 2022 ).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Most participants opined that HoloLens was helpful for learning; however, the results indicate that factors such as unfamiliarity with the English language version and lack of environmental support can negatively affect students’ immersive learning experience. Similar to studies in New Zealand and Ireland ( Collins & Ditzel, 2021 ; Saab, Hegarty, Murphy, & Landers, 2021 ), this study demonstrates that nursing education with MR learning has advantages, especially in allowing students to visualize a holographic image of a patient and practice care provision in a safe environment. Additionally, this finding highlights the potential of MR as a tool for enhancing patient care in nursing practice ( Saab et al, 2022 ).…”
Section: Discussionsupporting
confidence: 75%
“…Prior studies in nursing practice and education that evaluate the use of MR have demonstrated its potential benefits, including improved learning outcomes and satisfaction ( Collins & Ditzel, 2021 ). Mixed reality has been shown to enhance knowledge and clinical skills, like health assessment, clinical judgment, and communication ( Chen, Chen, Lee, Wang, & Sung, 2021 ; Frost, Delaney, & Fitzgerald, 2020 ; Kang & Kang, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…The MR experience has also been found to contribute to nursing student's clinical reasoning and judgement skills in 2019 research with the HoloLens (Collins and Ditzel 2021). It also helped the educators to assess a student's development so that they were able to customise the student's learning to further develop those skills.…”
Section: Benefits Of Mr In Trainingmentioning
confidence: 99%
“…The affordances of mMR to extend learning experiences include enhancing accessibility, authentic learning, collaborative professional practice, confidence and self-efficacy in clinical skills, cost-effectiveness (low fidelity), student feedback, motivation and engagement, repetitive practice for skill improvement, and clinical safety (Birt & Cowling, 2017;Cochrane et al, 2020;Cochrane et al, 2018;Collins & Ditzel, 2021;Hanson et al, 2020;Smith & Friel, 2021;Stretton et al, 2018;Yu et al, 2021).…”
Section: Why: Extend-ing Realitymentioning
confidence: 99%